Aspectuality across languages event construal in speech and gesture - Cienki, Alan J.; Iriskhanova, O. K. (Olʹga Kamaludinovna) (Human cognitive processing ;, 2018)
"The book provides a nuanced, multimodal perspective on how people express events via certain grammatical forms of verbs in speech and certain qualities of movement in manual gestures. The volume is the outcome of an international project that involved three teams: one each from France, Germany, and Russia, including scholars from the Netherlands and the United States. Aspect and gesture use are studied in three Indo-European languages, i.e. French, German, and Russian. The book also summarizes the main points and arguments from French, German, and Russian works on aspect in relation to tense, bringing these historical traditions together for an English-speaking reading audience. The work rekindles some fundamental theorizing about events and aspect, reinvigorating it in a new light with the use of recent theorizing from cognitive linguistics and cognitive psychology, as well as new research methods applied to new data from actual spoken, interactive language use. It illustrates the value of researching the variably multimodal nature of communication - as well as theoretical issues in connection with thinking for speaking and mental simulation - from an empirical point of view"--